Scalable Ir-Doped NiFe2O4/TiO2 Heterojunction Anode for Decentralized Saline Wastewater Treatment and H2 Production - Hong, Sukhwa; Kim, Jiseon; Park, Jaebeom; Im, Sunmi; Hoffmann, Michael R.; Cho, Kangwoo (Nano-Micro Letters, 2024)
Wastewater electrolysis cells (WECs) for decentralized wastewater treatment/reuse coupled with H2 production can reduce the carbon footprint associated with transportation of water, waste, and energy carrier. This study reports Ir-doped NiFe2O4 (NFI, 5 at% Ir) spinel layer with TiO2 overlayer (NFI/TiO2), as a scalable heterojunction anode for direct electrolysis of wastewater with circumneutral pH in a single-compartment cell. In dilute (0.1 M) NaCl solutions, the NFI/TiO2 marks superior activity and selectivity for chlorine evolution reaction, outperforming the benchmark IrO2. Robust operation in near-neutral pH was confirmed. Electroanalyses including operando X-ray absorption spectroscopy unveiled crucial roles of TiO2 which serves both as the primary site for Cl− chemisorption and a protective layer for NFI as an ohmic contact. Galvanostatic electrolysis of NH4+-laden synthetic wastewater demonstrated that NFI/TiO2 not only achieves quasi-stoichiometric NH4+-to-N2 conversion, but also enhances H2 generation efficiency with minimal competing reactions such as reduction of dissolved oxygen and reactive chlorine. The scaled-up WEC with NFI/TiO2 was demonstrated for electrolysis of toilet wastewater. Highlights: 1 Ir-doped NiFe2O4 (NFI) spinel with TiO2 heterojunction overlayer brought about outstanding chlorine evolution reaction in circumneutral pH. 2 Electroanalyses including operando X-ray absorption spectroscopy uncovered the active role of TiO2 for Cl− chemisorption. 3 NFI/TiO2 anode boosted both NH4+-to-N2 conversion and H2 generation in wastewater, and the practical applicability was confirmed with scaled-up anodes and real wastewater.